15 Is a dementia nurse specialist a feasible and acceptable way to improve care towards end of life in dementia?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Poole, Marie; Bamford, Claire; McLellan, Emma; Coe, Dorothy; Hrisos, Susan; Robinson, Louise; ,
Abstract : Background: End of life care for people with dementia is recognised as complex and often suboptimal. The SEED project (Supporting Excellence in End of Life Care) is a 5 year NIHR programme grant aimed at improving end of life care for people with dementia. Through research with key stakeholder groups, an intervention comprising of a Dementia Nurse Specialist (DNS) and supportive resources was developed. The DNS role was implemented for 12 months, with data collected alongside to assess the feasibility and acceptability of the role. Methods: A mixed methods approach was used to explore feasibility and acceptability. We focus on the qualitative process evaluation, which explored the views and experiences of: people with dementia; family carers; palliative specialists; mental health specialists; GPs; primary care specialists, care home staff; and the Dementia Nurse Specialists, through interview and observations Results: The role of a Dementia Nurse Specialist to improve care in advancing dementia was considered to be feasible and acceptable by all stakeholder groups. Key benefits identified were: the value of the role being based in primary care; the DNS role fits with existing services; the value of a specialist role to coordinate multidisciplinary care in dementia towards end of life; and the opportunities to build relationships with families, to facilitate advance planning conversations and provide timely support when needed. Additional factors were identified around the support needed to deliver the role and the key skills required. Conclusion: The DNS role was considered as feasible and acceptable as a way of improving the delivery of care towards end of life for people with dementia and their families. However, issues remain around the most effective way to implement the role in a context of scarce resources.